A stochastic model for tumour control probability that accounts for repair from sublethal damage - Ponce Bobadilla, Ana Victoria; Maini, Philip K.; Byrne, Helen (Mathematical medicine and biology, 2018)
Abstract. The tumour control probability (TCP) is the probability that a treatment regimen of radiation therapy (RT) eradicates all tumour cells in a given tis
Gesehen am 24.10.2019
Published: 26 February 2017